Stable isotope labelling of phosphatidylcholine synthesis in vivo in children with acute lung injury. (29th September 2015) - Goss, K; Ward, L; Ledger, V; Koster, G; Townsend, P; Burbidge-King, T; Marsh, M; Pappachan, J; Postle, A
Abstract : Background: Acute lung injury (ALI) is an inflammatory lung condition with significant morbidity and mortality, associated with surfactant dysfunction. Surfactant is a lipid–protein mixture composed of 80% phospholipid of which 35–55% is dipalmitoylphosphatidylcholine. The lipid profile of surfactant is significantly altered in patients with ALI, 1 but it is not clear whether this is due to decreased surfactant synthesis or increased degradation. Material and Methods: This study employs a novel method to quantify surfactant kinetics in children in vivo. Five children, aged 2 months to 3 years, admitted to the paediatric intensive care unit with a clinical diagnosis of ALI, were infused with methyl-D9 choline chloride. Synthesis of phosphatidylcholine (PC) in sequential lung bronchoalveolar lavage (BAL) and serum samples were analysed by electrospray ionisation tandem mass spectrometry. Results: Measurable incorporation of methyl-D9 choline chloride into both surfactant and serum PC was demonstrated, with peak incorporations of 0.7±0.08% in BAL fluid (BALF) (figure 1 ) and 3.0±0.8% in serum (figure 2 ). The rate of surfactant synthesis varied widely and did not correlate with respective measurement of serum PC synthesis, highlighting lung and systemic effects of ALI. Conclusion: This study demonstrates the feasibility of methyl-D9 choline chloride labelling to quantify kinetics of surfactant and serum PC synthesis in children with ALI in vivo. The variation in BALF PC synthesis indicates a wide range of surfactant synthesis/secretion, while comparison with serum PC synthesis suggests that much of this variation is lung specific.